2008
DOI: 10.1213/ane.0b013e318167ab1f
|View full text |Cite
|
Sign up to set email alerts
|

Does the Pleth Variability Index Indicate the Respiratory-Induced Variation in the Plethysmogram and Arterial Pressure Waveforms?

Abstract: This study is the first to demonstrate the ability of PVI, an index automatically derived from the pulse oximeter waveform analysis, to automatically and continuously monitor deltaPOP. This new index has potential clinical applications for noninvasive fluid responsiveness monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 17 publications
2
103
1
2
Order By: Relevance
“…Studies have shown the usefulness of this noninvasive dynamic parameter in mechanically ventilated patients in the operating room and in the intensive care unit (ICU). 6,10,19 Conversely, other studies have concluded that PVI was of limited value in predicting fluid responsiveness in laparoscopic surgery 20 and in the ICU setting, respectively. 21 Several observations have shown the limitations of this parameter.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown the usefulness of this noninvasive dynamic parameter in mechanically ventilated patients in the operating room and in the intensive care unit (ICU). 6,10,19 Conversely, other studies have concluded that PVI was of limited value in predicting fluid responsiveness in laparoscopic surgery 20 and in the ICU setting, respectively. 21 Several observations have shown the limitations of this parameter.…”
Section: Discussionmentioning
confidence: 96%
“…Another new device (Masimo Radical TM 7 system, Masimo Co., Irvine, CA, USA) can automatically display perfusion index (PI) and calculate the pleth variability index (PVI), which is a new algorithm that automatically calculates 螖POP. But the ability of PVI to predict fluid responsiveness was evaluated in mechanically ventilated patients preoperatively (12)(13)(14) or after passive leg rising in spontaneously breathing volunteers (15). Whether these two indices can be used for intraoperative fluid responsiveness predictions and fluid optimization in patients undergoing major surgical procedures still has to be demonstrated, and the optimal threshold value of these indices in the surgical setting still has to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…PI depends on vasomotor tone and sympathetic tone, which may affect the pulsatile absorption component (23 (14). This may be related to a decrease in sympathetic tone related to general anaesthesia and vasomotor tone does not impact PVI (12,13). The accuracy of PVI to predict fluid responsiveness was improved on analyzing patients with higher PI values (25).…”
Section: Changes In Hemodynamic Variables After Volume Expansionmentioning
confidence: 99%
“…A recent meta-analysis [66] concluded that PVI had acceptable reliability in predicting fluid responsiveness in ventilated patients. However, changes in vasomotor tone, vasopressors administration, and other conditions such as hypothermia have a direct impact on the plethysmographic waveform and should be well known as its potential limitations [67,68]. Consequently, PVI should continue to be analyzed under stable and unstable conditions in order to more accurately determine the specific limitations.…”
Section: Plethysmographymentioning
confidence: 99%